DETERMINANTS OF UNMET HEALTHCARE NEEDS IN THE EUROPEAN UNION COUNTRIES - Gutium, Tatiana; Gojaeva, Elmira (Economy and Sociology, 2024)
The population’s access to quality medical services is one of the indicators that reflects the country’s level of development from a social point of view. The quality of life of citizens largely depends on their health status. No matter how rich he may be, a sick person cannot fully enjoy life. The rate of population aging in the EU countries is high; with age, chronic diseases appear, and the need for medical care increases. Therefore, the object of study, “unmet need for medical examination and care,” is relevant. The study’s main objective is to verify the hypothesis that the number of practicing doctors, dentists, and the number of hospital beds influence the “unmet need for medical examination and care,” and by applying software EViews 9.5 it was established the type of correlation between the endogenous variable “unmet need for medical examination and care” and the exogenous variables: the number of practicing doctors, dentists and the number of hospital beds. Regression analysis was applied to achieve the proposed goal. The indicator “unmet need for medical examination and care” indicates that citizens’ dissatisfaction with the medical services provided in every second member state of the European Union has increased over the past five years. However, in other EU countries, the number of people satisfied with the availability and quality of health services is growing. In most EU countries, except four countries, the number of hospital beds per hundred thousand inhabitants and hospitals has decreased in the last twelve years. Despite the surge in the disease during the COVID-19 pandemic, the downward trend continues. Thus, in some EU countries, there is a steady downward trend in patient satisfaction with accessibility and quality of medical care. The results obtained in this study allow us to accept the hypothesis that the number of practicing doctors, dentists, and the number of hospital beds influence the “unmet need for medical examination and care.” It was also determined that in comparison with other countries, in the case of France, the regression coefficient between the number of doctors and the “unmet need for medical examination and care” is the largest (by module).